2015
DOI: 10.1139/cjfr-2014-0512
|View full text |Cite
|
Sign up to set email alerts
|

Towards silvicultural mitigation of the European ash (Fraxinus excelsior) dieback: the importance of acclimated trees in retention forestry

Abstract: The European ash (Fraxinus excelsior L.) dieback is an acute forest pathology problem caused by the invasive ascomycete Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz, Hosoya. There are no practical solutions yet, but selection for resistant genotypes and intensive care have been highlighted as options. Our aim was to assess the disease mitigation potential of silvicultural harvests, which influence stress levels in retained trees. We annually monitored 577 retention trees on Estonian cut areas for 13 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
15
0
3
Order By: Relevance
“…But Rosenvald et al . () did not find Armillaria spp. contributing to the death of isolated retention trees.…”
Section: Herbivory and Diseasementioning
confidence: 88%
See 2 more Smart Citations
“…But Rosenvald et al . () did not find Armillaria spp. contributing to the death of isolated retention trees.…”
Section: Herbivory and Diseasementioning
confidence: 88%
“…(Bakys et al 2011) or environmental stresses (Bakys et al 2009a,b;Schumacher, Kehr & Leonhard 2010) exacerbated by ash dieback-infected ash having narrower vessels in the xylem (reducing from 0.15 mm in healthy to 0.12 mm in infected trees) with consequent reduced hydraulic conductivity (Tulik, Marciszewska & Adamczyk 2010). But Rosenvald et al (2015) did not find Armillaria spp. contributing to the death of isolated retention trees.…”
Section: Ash Diebackmentioning
confidence: 96%
See 1 more Smart Citation
“…Several authors showed that high moisture promote ash dieback (Husson et al 2012;Marçais et al 2016) and it has been hypothesized that dense stocking could favour disease severity by enhancing air humidity (Havrdová et al 2017). Rosenvald et al (2015) showed trees in stand edge were less affected by H. fraxineus and hypothesised that high temperatures could limit the disease development in these environments. Last, high summer temperature were demonstrated to limit ash dieback was in the Rhône valley in France at the southern limit of the disease presence .…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the impact of host density on the disease severity have been conflicting (Skovsgaard et al 2017). Nevertheless, it is clear that dense stands with a closed canopy are very susceptible to the fungus while ashes set up in open habitats or near forest edges appears to be less affected (Havrdová and Cerný 2013;Rosenvald et al 2015;Vacek et al 2015). H. fraxineus has also been shown to have a poor survival at temperatures above 35°C, which affects the disease epidemiology (Hauptman et al 2013.…”
Section: Introductionmentioning
confidence: 99%